Ethnopharmacology Potentials of Mangrove Bulalo, North Gorontalo - Ernikawati; Daud Sandalayuk; Alexander Ruruh; Zeinab Nurlela Y. Suma (Postgraduate, University of Mataram, 2023)
Ethnopharmacology is the study of the practical utilization of mangrove plants which have been used as a source of traditional medicine by people living in certain areas since ancient times for generations. This study aims to determine the diversity of mangrove species as the ethnopharmacology of Bulalo, Kwandang District, North Gorontalo. The research was conducted from March to May 2023. The method used in this study was semi-structured interviews. The results showed that species that have the potential for ethnopharmacology are widely used by local people as traditional medicines. Based on the results of interviews with the local community, of the 14 ethnopharmacological species found in Bulalo Village, 7 species have medicinal properties and have been used as traditional medicines by the community for generations, such as Avicennia alba, Bruguiera gymnorriza, Ceriops decandra, Rhizophora apiculate, Rhizophora mucronate, Rhizophora stylosa, and Sonneratia casseolaris, which has been used as a medicine containing phytochemical compounds such as alkaloids, saponins, terpenoids, flavonoids, and phenols. The parts used in traditional medicine are the fruit, leaves, and sap. The ways to use it include hypertension, hepatitis, asthma, flatulence, recovering energy after giving birth, mouth sores, malaria, dysentery, ulcers, cholera, sore eyes, itching, internal injuries, boils, healing burns, and bruises.